2021
DOI: 10.3390/su132111799
|View full text |Cite
|
Sign up to set email alerts
|

Family Business, Resilience, and Ethnic Tourism in Yunnan, China

Abstract: The expansion in commodification through tourism and the transformation of communities and heritages into destination attributes have become the centre of tourism research facing the COVID-19 crisis. Since small family businesses comprise the majority of the tourism industry, theories and practices on surviving the crisis are urgently required. This research attempts to clarify the level of business resilience during the COVID-19 lock down when business can only be conducted at home with very few visitors. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…By extracting key terms used in formulating definitions, it becomes noticeable that most authors (22 out of 23 papers) continuously focus on disruptions or crises faced by the organization. Adapting to emerging circumstances is an essential process (Lin and Wen, 2021; Sarkar and Clegg, 2021), according to more than half of the papers analysed. However, different from the pre-COVID era, preparedness and anticipation no longer constitute a major part in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…By extracting key terms used in formulating definitions, it becomes noticeable that most authors (22 out of 23 papers) continuously focus on disruptions or crises faced by the organization. Adapting to emerging circumstances is an essential process (Lin and Wen, 2021; Sarkar and Clegg, 2021), according to more than half of the papers analysed. However, different from the pre-COVID era, preparedness and anticipation no longer constitute a major part in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on the strategic renewal capacity, several studies scrutinized the time before a discontinuous event and analyzed family firms’ processes aiming to reduce firm vulnerability and/or increase its ability to respond to disruptions (Crespi-Vallbona & Plana-Farran, 2022; Demmer et al, 2011; Doeksen & Symes, 2015). Further studies found that family businesses used proactive strategies to increase resilience: By seizing market opportunities, they changed and/or innovated before adversity occurred and thus reduced risks and were prepared for future adverse events (e.g., González & Pérez-Uribe, 2021; Lin & Wen, 2021).…”
Section: Unveiling the Distinctive Dimensions Of Family Business Resi...mentioning
confidence: 99%
“…Sejauh ini, bisnis model untuk mengembangkan usaha kuliner lebih banyak memperdebatkan isu tentang franchise untuk meningkatkan ekonomi dan pendapatan (Al Adresi & Darun, 2017;Bulilan, 2021;Utami et al, 2019). Tren ini merupakan implikasi dari persaingan bisnis dalam model pengembangan usaha kecil menengah di Indonesia yang sebagian besar berpendapat bahwa model bisnis tersebut dapat meningkatkan pendapatan negara maupun kesejahteraan bagi pelakunya (Kinyua, 2014;Lin & Wen, 2021;Van Stel et al, 2007). Namun sebagian juga berpendapat bahwa model pengembangan usaha kecil menengah tidak semata-mata mampu bangkit karena persoalan regulasi, modal, kemampuan personal dalam mengembangkan usaha, dan kalah bersaing dengan pelaku usaha yang memiliki kapital besar (Arif, 2008;Dani, 2013).…”
Section: Pendahuluanunclassified